Features of the text field of the First Psalm of Psalter in Czech and Polish tradition - Anikina, Tatiana; Grigorieva, Lidia (Bohemistyka, 2019)
This article is about comparing the transcriptions of Psalm 1 in Psalter into Czech and Polish. The Bible kralická, the Czech ecumenist translation, the translation of Fajman representing the Czech hymnological tradition and the transcriptions of psalms into Polish by Jakub Wujek, Jan Kochanowski and Czesław Miłosz are considered. The stylistic analysis suggests that the Hussite tradition is strong in Czech hymnology. The latter suggests utmost simplicity and accessibility of understanding of biblical texts. Polish tradition preserves the ambiguity of biblical word, and the associated ambiguity in interpretation of the nuances of biblical text. The arrangements of Kochanowski employ more complex metaphoricity and tend to clarify the text of the Psalm.